Analyzing the Relationship Between Empathic Tendencies, DecisionMaking Styles and Communication Skills of Faculty of Sport Sciences Students - CENGİZ, Recep and SUNAY, Hakan and KAYA, Bayram (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2022)
The aim of this study was to examine the relationship between the empathic tendency, decisionmaking styles and communication skills of university students in a sample of faculty of sport sciences. The study sample was consisted of 370 faculty of sport sciences students from Manisa Celal Bayar University. In the study, the data were collected with the Melbourne Decision-Making Scale I-II, Empathic Tendency Scale and Communication Skills Scale, as well as the personal information form designed by the researchers. Statistical package program was used in the analysis of the data. The distribution of the personal information of the participants was determined by percentage and frequency methods. The normality of the data was determined by the Kolmogorow-Smirnow test and the Spearman Correlation test was used to determine the relationships between the variables. According to analyzed results, a weak and negative relationship was found between the empathic tendencies of the female participants and their communication skills, while a weak but positive relationship was found with their decision-making styles. On the other hand, no significant relationship was found between the empathic tendencies of male participants and their communication skills however, weak negative correlations were found with their decision-making styles. As a conclusion, the present study showed that there were various relationships between the empathic tendencies, decision-making styles and communication skills of both male and female students of the faculty of sports sciences. However, more research is needed to examine the present results in depth.